Integration of antagonistic rhizobacteria and soil solarization for the management of bacterial wilt of tomato caused by Ralstonia solanacearum - A.K. SOOD, PRADEEP KUMAR and (Indian Phytopathology, 2002)
Soil solarization for 8 and 10 weeks during March to May increased soil temperature at 5 cm depth in wilt sick plots at Palampur by 5.2Â°C and 6.2Â°C during 1998 and 1999, respectively. The increased soil temperature promoted abundant germination and profuse growth of weeds in the tarped (solarized) plots during early stages of traping followed by their complete death by burning later on in both the 8 and 10 weeks solarized plots. The bacterial wilt incidence in such plots was significantly suppressed by 65.9% and 71.6% during 1998 and 68.9% and 73.4% in 1999 in 8 and 10 weeks of solarization, respectively as compared to 97.7% and 86.9% wilt in the non solarized plots. The significant reduction in wilt incidence was attributed to the incorporation of antagonistic rhizobacteria (Pseudomonas fluorescens and Bacillus cereus) in soil prior to solarization as the population of the antagonists was considerably enhanced after solarization whereas that of Ralstonia solanacearum was significantly reduced and also resulted in increased vigour of tomato plants in solarized plots as compared to non solarized plots.